2021
DOI: 10.3390/cancers13153879
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Characteristics of Pregnancy-Related Meningiomas

Abstract: Meningiomas are the most common intracranial tumor. During pregnancy, explosive growth of a known meningioma occasionally occurs, but the underlying reasons remain unknown. Prolactin has been suggested as a possible key contributor to pregnancy-related meningioma growth. This study sets out to investigate prolactin and prolactin receptor status in 29 patients with pregnancy-related meningiomas in Denmark, from January 1972 to December 2016, as compared to 68 controls aged 20–45 years, also undergoing resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, it is controversial whether the growth of meningiomas during pregnancy is only due to the expression of PR. A study of the pathology of meningiomas during pregnancy found that the frequency of PR positivity during pregnancy was similar with the control group (6,10). Meningioma growth during pregnancy have the possibility to be affected by not only hormone receptor expression but also tumor location (6,11).…”
Section: Discussionmentioning
confidence: 89%
“…However, it is controversial whether the growth of meningiomas during pregnancy is only due to the expression of PR. A study of the pathology of meningiomas during pregnancy found that the frequency of PR positivity during pregnancy was similar with the control group (6,10). Meningioma growth during pregnancy have the possibility to be affected by not only hormone receptor expression but also tumor location (6,11).…”
Section: Discussionmentioning
confidence: 89%
“…From them, losses on TIMP3 (22q) have been suggested to take part in reduced apoptosis [ 30 , 31 ] or angiogenesis [ 32 ], and our finding supports the extensive belief that additional genes located on 22q should contribute to MN tumorigenesis [ 3 , 4 ]. The influence of estrogens in MN has been widely discussed on MN, with many discrepancies in the literature but little has been described at the genetic level [ 33 , 34 ]. Both ESR1 and PARK2 are located in a frequently altered chromosomal region in MN (6q), and both display effects over the Wtn/b-catenin pathway [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Recently, a dose-dependent relationship between the growth of a subgroup of meningiomas and treatment with cyproterone acetate has been detected. 35 Reproductive factors and risk of meningioma development are not thoroughly elucidated, [36][37][38] and hormonal therapies in meningioma have not shown substantial effect. 39,40 The WHO classification system-meningiomas then and now…”
Section: Epidemiology and Aetiologymentioning
confidence: 99%